Tunus'ta bir Osmanlı yapısı Sidi İbrahim Siyahi Zaviyesi - Skander, May (Fatih Sultan Mehmet Vakıf Üniversitesi, Mühendislik ve Fen Bilimleri Enstitüsü, 2018)
Tunus şehri, köklü tarihiyle gerçek bir kültür ve mimari mozaiğe sahiptir. Halk arasında “Medina” olarak tabir edilen şehirde, sokaklar, konutlar ve pazarlar sayesinde, zengin bir tarihi miras ve mimari tabakalaşma görülmektedir. Bu durum, bugün şehrin simgesi olmuştur. Öte yandan, Osmanlı İmparatorluğu’nun en önemli şehri olan İstanbul, özgün mimarisi ile bulunduğu çağın estetik ve tekniğinin hünerlerini her daim yansıtmıştır. Bu iki şehrin mecazi olarak birleşimi özellikle Arap, Endülüs ve Osmanlı miraslarının kesişimlerini taşıdığı için detaylandırılmış bir mimarinin ortaya çıkmasına yol açmıştır. Tezde bahsedilen Sidi İbrahim Riyahi Zaviyesi, eski şehir Tunus’un batısında yer almaktadır. Osmanlı şehri Tunus’un çiçek devri olarak kabul edilen 19. Yüzyılın ortasında inşa edilen ve diğer dini binalar arasında kendi dinini ve kültürünü farkettiren bir yapıdır; fakat daha önemlisi özgün bir mimari karaktere sahiptir. Sidi İbrahim Riyahi Zaviyesi’nin ibadet pratikleri İstanbul tekke ve zaviyeleri ile farklılık gösterir. Ancak tasavvufun kavramsal çerçevesine sıkıca bağlı şekilde tıpkı İstanbul tekke ve zaviyelerinde olduğu gibi, kendi ibadet alanlarının özelliklerini taşıyan mekanlara sahiptir. Yapının bütün mekanları ve bu mekanların mimari unsurları gösteriyor ki, Tunus ve Osmanlı sanatının esintileri ve sembolleri zaviyenın gizemli felsefesinde harmanlanmıştır. Binanın özelliklerini en iyi yansıtan mekan, “semahane” adı verilen ibadet odasıdır. Basit bir dikdörtgen formunda olan bu mekan, zengin süslemeleri, dekorasyonunun bolluğu ve üzerini örten kubbesinin anıtsallığıyla öne çıkmaktadır. Tezin amacı, Sidi İbrahim Riyahi Zaviye'sinin rölöve ve restitüsyon projelerini oluşturmak ve restorasyon çalışması ile alakalı akla gelmesi muhtemel sorulara cevap olabilecek bir restorasyon önerisi sunmaktır. Aynı amaç doğrultusunda bina hakkında doğru bir veri tabanı oluşturmak için, birkaç değişik araştırma yöntemi, çeşitli görseller ve dökümanlar kullanılmıştır. Bu dökümanların tesbitine binada yapılan x kapsamlı bir rölöve çalışması ile başlanmıştır. Tunus’da tarihi eserleri korumakla görevli kurumlar ile görüşülerek, mekanda çalışma yapmak için iki aylık izin alınmıştır Tez, Tunus şehrinin tarihi merkezinde yer alan dini mekanların Osmanlı Devri’ndeki mimarisi hakkında bilgi vermenin yanında, Sidi İbrahim Riyahi Zaviyesi’nin ileri bir tarihte geçirmesi muhtemel bir restorasyon uygulaması için belge özelliği taşımaktadır. Aynı çerçevede, zaviye dahilinde bir mekanın, hem yapıyı korumak maksadıyla hem de Sidi İbrahim’in torunlarının isteği üzerine kütüphane olarak yeniden işlevlendirilmesi önerilerek detaylandırılmıştır.

The concept of identity, exposed to us in its most clear forms by the historical architecture, constitute in reality an amalgam of paradigms and roots that proves civilisations not only were a successive evolution for human’s urban settlements and architectural acheivements but also a recipient of knowledge’s gathering and exchanges. With a long historical background to look upon, the nowadays city of Tunis describes a true mosaic of cultural and architectural mixture. İts old city called in common dialect “Medina”, shows within its streets, residences and bazars the signs of a rich historical and more specificly architectural stratification that has become today a trade-mark in itself. The Ottoman Empire on the other side with its key city İstanbul, had been developping througout five centuries an outstandingly unique architecture that is coutinuously regarded as one of the modern ages’ prowesses in matters of aestheticity and technicality. The symbiosis of these two particular cities’ cultural charactersistics in Tunisa, metaphorically carried by the cultural encouter between Arabic, Andalousian and Ottoman legacies can only give way to the appearance of particularly elaborated architecture. İn this context, the Zawiya (mystic lodge) of Sidi İbrahim Riyahi situated in the Western neighbourhood of the old city of Tunis, build around the middle of the nineteeth century at what is considered as a flowered age of the Tunisian Ottoman Province, stand out among other religious building by its religous and cutural influence, but moreover by it architectural and artistical characteristicals. Tightly linked to the conceptual frame of the mysticism, the building though holding different ritual practices from the ones observed in the Derviches’ Lodges of İstanbul, expresses its functional attributes in a similar spatial manner. From the distinctive way with which the building is accessed to until the organization of the differente spaces arount the central court, the architectural elements reveal the influences of both the xii intrinsic tunisian art and the ottoman inspirations that are tangled with the symbols of the mystic philosophy adopted in the Zawiya. The building main feature resides in the principle chamber called “Samahane” that means the room of prayers. The space that presents a simple rectangular plan stikes by the complexity and the profusion of its décorations and the monumentality of the dome that is covering it. The aims of this thesis is to issue a possible answer to the conservation of this building by producing an essay of restoration. Several research tools and processes have been employed to fullfill this purpose as well as to output a set of documets and graphics that are intented to constitute an accurate database to the structure. The developpment of these documents obviously started with a building site seeing. To accomplish this mission, a number of permits given by the official authorities had to be allocated, meeting with the responsibles of the historical conservation units had to be carried out and a full time work during two months had to be scheduled on site in Tunis. The importance of this research on the other hand lay on the fact that il will not only grant a sum of material information about the traditional architecture of religious stuctures in the old town of Tunis during the Ottoman sovereignty, but it will also constitute an archive to The Sidi İbrahim Riyahi Lodge that can be consulted and examined for eventual future interventions. İn this same order of ideas indeed, the attempt at giving the building a new functional purpose which is a library has all but emerges from an actual intent of the family of the late Sidi İbrahim, to push back the risks of disfunctions in the building and allow its sustainability. Keywords: Tunis. Old city, historical buildings, conservation, restoration, Ottoman period, influences, derviche lodges, mysticism, traditional architecture.
FSM Vakıf Üniversitesi, Mühendislik ve Fen Bilimleri Enstitüsü